This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Assuming that lo g is the common log, i.e., base 10, take log of both sides to get
lo g ( x ) ∗ lo g ( x ) = lo g ( 1 0 0 0 ) + 2 lo g ( x ) = 3 + 2 lo g ( x ) .
Letting a = lo g ( x ) the equation becomes
a 2 − 2 a − 3 = 0 ⟹ ( a − 3 ) ( a + 1 ) = 0 .
So the solutions are
a = lo g ( x ) = 3 ⟹ x = 1 0 3 = 1 0 0 0 and
a = lo g ( x ) = − 1 ⟹ x = 1 0 − 1 = 1 0 1 .
Now as we are looking for an integer, after confirming that x = 1 0 0 0 does indeed satisfy the original equation we can conclude that the answer is x = 1 0 0 0 .